English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I used the integrating factor method and got

d/dx (ye^x) = sin(e^-x) + (e^x)(cos(e^-x)) - e^(-x)

Now comes the problem, how do you integrate sin(e^-x) ?

2007-02-06 17:58:08 · 3 answers · asked by sky_blue 1 in Science & Mathematics Mathematics

3 answers

♠ Let’s brush it first: t=exp(-x) and x=-ln(t) and dx=-dt/t;
thus your equation looks:
dy/t = -(sint +cost/t –t –y/t)dt/t; t·y’= -t·sint –cost +t·t +y;
♣ t·y’-y= -t·sint -cost +tt; (t·y’-y)/tt = 1-sint/t –cost/tt; (y/t)’ =1-sint/t –cost/tt;
♦ thus y/t =t -s1-s2, where s1=∫dt·sint/t, s2=∫dt·cost/tt;
♥ now run your fingers and do find s1 with s2. When done the result will be near. If embarrassed again just click my name and write me, you are welcome!

2007-02-06 23:39:59 · answer #1 · answered by Anonymous · 0 0

If you make the change z= e^-x dz = -e^-x dx so dx=-dz/z You come to
Integral -sin(z)/(z)*dz which can not be written as a combination of so called elementary functions

2007-02-07 06:01:48 · answer #2 · answered by santmann2002 7 · 0 0

isn't it just cos(e^-x) * e^-x?

2007-02-07 02:34:58 · answer #3 · answered by Jian C 3 · 0 0

fedest.com, questions and answers